2018
DOI: 10.3892/or.2018.6746
|View full text |Cite
|
Sign up to set email alerts
|

Text mining‑based drug discovery in cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma (cSCC) is one of the most common skin cancers. However, the efficacy and utility of the available drug therapies are limited. The objective of the present study was to determine the genes and molecular pathways associated with cSCC by using computational tools and publicly available data, and to explore drugs targeting the relevant molecular pathways for cSCC treatment. In this study, we used text mining and GeneCodis to mine genes which were highly related to cSCC. Protein-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…DrugQuest is a website that applies text-mining technologies and the TextQuest algorithm to mine a publicly accessible database to identify biologically significant terms and group these words based on the textual content (29). Another cancer-related study demonstrated using text-mining and pathway analysis tools is a prospective method for exploring potential drugs targeting the genes or pathways related to cutaneous squamous cell carcinoma (cSCC) (30). In this study, 121 genes relevant to cSCC were identified using a text-mining approach, and 55 drugs were revealed that could target 10 pathways through gene enrichment analysis.…”
Section: Editorial Commentarymentioning
confidence: 99%
“…DrugQuest is a website that applies text-mining technologies and the TextQuest algorithm to mine a publicly accessible database to identify biologically significant terms and group these words based on the textual content (29). Another cancer-related study demonstrated using text-mining and pathway analysis tools is a prospective method for exploring potential drugs targeting the genes or pathways related to cutaneous squamous cell carcinoma (cSCC) (30). In this study, 121 genes relevant to cSCC were identified using a text-mining approach, and 55 drugs were revealed that could target 10 pathways through gene enrichment analysis.…”
Section: Editorial Commentarymentioning
confidence: 99%
“…e text mining methods [16,17] including information matching and other retrieval technologies are limited by the mining algorithms to detect new interactions in the literature database. However, proteins metastructure provides a new biologic way to describe the proteins with primary sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, our goal was to retrieve DDAs while lifting the strain on establishing or possessing prior gene-disease lists, and we concentrated herein on cancer with a particular focus on Blood Cancers (BCs). Cancer is a complex and multifactorial disease for which there is a widespread availability of related literature [ 5 ], useful for biomarker research [ 6 ], drug discovery [ 7 ], biological pathways detection [ 8 ], among others, highlighting this technique's positive contribution to a highly demanding field of study. The strength of mining the literature towards building disease networks was tapped into on multiple occasions as recently reviewed by Rodríguez-González [ 9 ].…”
Section: Introductionmentioning
confidence: 99%